Apert syndrome with glucose-6-phosphate dehydrogenase deficiency: a case report - G. TOSUN & Y. SENER (Paediatric Dentistry, 2006)
Apert syndrome is characterized by midface hypoplasia, syndactyly of the hands and feet, proptosis of eyes,steep and flat frontal bones, and premature union of cranial sutures.